Peran Pemerintah Desa Wemeda Kecamatan Malaka Timur Kabupaten Malaka Terhadap Perlindungan Sumber Daya Air Di Tinjau Dari Undang-Undang Nomor 17 Tahun 2019 Tentang Sumber Daya Air - Muti, Odilia Maria Roswita; Nuban, Detji K E R; Asnawi, Norani (Law Faculty, Nusa Cendana University, 2025)
This study examines the role of the Wemeda Village Government in protecting Wemetan water resources in accordance with Law No. 17/2019 concerning Water Resources. Using empirical legal research and qualitative descriptive approaches, data were collected through interviews, observations, and document analysis involving 424 heads of families. The findings show that although the village government has implemented conservation efforts such as reforestation, pipe maintenance, and community involvement, their authority remains limited because the main responsibility for water management lies with the Malaka Regency Government. The main challenges faced include: (1) frequent pipe damage and power outages, (2) lack of socialization regarding water protection regulations, and (3) lack of institutional support (no Regional Technical Implementation Unit/UPTD). Despite receiving funds of IDR 19.3 billion, water distribution is still inefficient (only twice a week), forcing residents to buy tanker water at high prices (IDR 150,000-200,000/tank). This study highlights three crucial gaps: (1) a disconnect between national laws and local implementation, (2) weak intergovernmental coordination, and (3) the absence of binding village regulations (Perdes) for law enforcement. Proposed recommendations include the establishment of UPTDs, improved infrastructure maintenance, and more intensive community education.